Reconstruction of a maxillectomy and rhinectomy defect utilising a novel subperiosteal prosthesis and magnet-retained nasal prosthesis: A case report. (December 2022) - Gunawardena, Dulan A.; Howes, Dale; Fleming, Sophie; Clark, Jonathan; Leinkram, David; Palme, Carsten; Dusseldorp, Joseph R.; ,; ,
Highlights: Reconstruction using autologous tissue can prove difficult in the setting of recurrent cancerous disease. Herein we describe a novel, custom-made subperiosteal prosthesis to support a magnet retained nasal prosthesis and upper jaw denture post left maxillectomy and total rhinectomy. Prosthetic integration with craniofacial implants are effective, alternative approaches in the setting of multiple previous ablative and reconstructive procedures.